Fluorosilicone rubber fireproof cable sheath and preparation method thereof

CN123004147APending Publication Date: 2026-10-30GUANGZHOU ZHUJIANG CABLE CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611213771.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

石墨烯片层易发生团聚堆叠,难以构建连续均匀有效的阻隔网络,预期延缓电解液渗透、力学补强效果无法稳定发挥;同时团聚石墨烯相互搭接易形成导电通路,造成护套局部导电、介电击穿强度下降,违背高压电缆护套绝缘使用要求,并且石墨烯分散状态难以稳定控制,制品性能波动大,量产稳定性不足

Benefits of technology

1、本申请通过构建“硅酸铝片层物理隔离石墨烯、白炭黑颗粒填充片层搭接缝隙”的一体化杂化填料结构,从源头阻断石墨烯导电通路,同时以二维片材交错排布形成的迷宫阻隔网络延长电解液渗透路径,并与无卤复配阻燃填料协同成炭,同步提升了护套的绝缘性、耐电解液性和阻燃性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application relates to the technical field of cable sheaths, and particularly discloses a fluorosilicone rubber fireproof cable sheath and a preparation method thereof. The fluorosilicone rubber fireproof cable sheath comprises the following raw materials in parts by weight: fluorosilicone raw rubber 100 parts, active magnesium oxide 1-3 parts, graphene-aluminum silicate-white carbon black in-situ hybrid intercalation filler 1-4 parts, halogen-free compound flame-retardant filler 12-22 parts, fluorosilicone oil 0.6-1.2 parts, double-25 vulcanizing agent 0.4-1.2 parts and TAIC crosslinking agent 0.8-1.6 parts. The graphene-aluminum silicate-white carbon black in-situ hybrid intercalation filler can avoid mutual lapping of graphene sheet layers to form a conductive path, guarantee high-voltage insulation reliability, and at the same time, two-dimensional sheet layers are staggered to prolong electrolyte penetration paths, and synergistic carbonization under high temperature improves the flame-retardant performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of cable sheath technology, and more specifically, to a fluorosilicone rubber fireproof cable sheath and its preparation method. Background Technology

[0002] With the rapid development of the new energy industry, high-end equipment, and rail transit, high-voltage electrical equipment cables face multiple stringent requirements for sheath materials. Cable sheaths not only need stable electrical insulation performance and resistance to chemical corrosion, but also excellent fire-retardant properties to ensure short-term safe operation of the line under conditions of short-circuit fire and media leakage. Fluorosilicone rubber combines the excellent low-temperature toughness and weather resistance of silicone rubber with the solvent resistance of fluororubber, making it a preferred base material for high-end special cable sheaths. The industry has already begun developing formulations for fluorosilicone rubber sheaths.

[0003] In existing technologies, such as the patent application CN122037583A, a battery-resistant fluorosilicone rubber high-voltage cable sheath material for vehicles is disclosed. This material uses graphene to extend the electrolyte penetration path through a labyrinthine barrier effect, reducing the rate at which leaked electrolyte from the power battery penetrates into the sheath, thus achieving cable protection and rubber reinforcement. However, the formulation directly adds graphene without insulation treatment or dispersing agents. Graphene sheets are prone to agglomeration and stacking, making it difficult to construct a continuous, uniform, and effective barrier network. The expected effects of delaying electrolyte penetration and mechanical reinforcement cannot be consistently achieved. Furthermore, the overlapping of agglomerated graphene sheets easily forms conductive pathways, causing localized conductivity and a decrease in dielectric breakdown strength in the sheath, violating the insulation requirements for high-voltage cable sheaths. Moreover, the graphene dispersion state is difficult to control stably, resulting in large fluctuations in product performance and insufficient mass production stability. Summary of the Invention

[0004] To improve the insulation of cable sheaths, this application provides a fluorosilicone rubber fireproof cable sheath and its preparation method.

[0005] In the first aspect, this application provides a fluorosilicone rubber fireproof cable sheath, which adopts the following technical solution: A fluorosilicone rubber fireproof cable sheath comprises the following raw materials in parts by weight: 100 parts fluorosilicone raw rubber, 1-3 parts activated magnesium oxide, 1-4 parts graphene-alumina silica-furan black in-situ hybrid intercalation filler, 12-22 parts halogen-free compound flame retardant filler, 0.6-1.2 parts fluorosilicone oil, 0.4-1.2 parts bis(2,5)-5-sulfurizing agent, and 0.8-1.6 parts TAIC crosslinking agent; The preparation method of the graphene-alumina silicate-fumed silica in-situ hybrid intercalation filler is as follows: In an ethanol-water solution system, ultrasonic synergistic stirring is used to promote the intercalation of sheet-like alumina silicate into the spaces between graphene sheets, while hydrophobic vapor-phase fumed silica nanoparticles are simultaneously anchored at the gaps between the sheets. After being modified by fluorosilane grafting, the filler is dried and pulverized to obtain a ternary hybrid insulating barrier filler.

[0006] This application introduces a pre-fabricated graphene-alumina silicate-fumed silica in-situ hybrid intercalation filler. Two-dimensional sheet-like alumina silicate is intercalated between the graphene sheets, physically isolating them. Fumed silica nanoparticles are embedded in the gaps formed by the overlap between the graphene and alumina silicate sheets, filling and sealing any remaining contact sites. Due to this structure, the graphene sheets are difficult to overlap and form electron transport channels, allowing the rubber compound to maintain a high volume resistivity even after the introduction of the hybrid filler. Simultaneously, the staggered arrangement of graphene and alumina silicate sheets within the rubber matrix forces the permeating medium to diffuse along the tortuous channels between the sheets, effectively extending the path length for the electrolyte to penetrate from the outside of the sheath to the inside. Under high-temperature conditions, alumina silicate promotes carbonization of the matrix, while graphene enhances the strength of the carbon layer. These two materials, combined with the halogen-free composite flame-retardant filler, ultimately improve the insulation and flame retardancy of the sheath.

[0007] Preferably, the preparation method of the graphene-alumina silicate-fumed silica in-situ hybrid intercalation filler includes the following steps: (1) Add graphene to an aqueous ethanol solution and disperse it by ultrasonication to obtain a dispersion; (2) Add flake aluminum silicate and hydrophobic fumed silica to the dispersion, and treat for 2-4 hours at an ultrasonic power of 200-500W and a stirring rate of 300-800rpm to obtain a ternary hybrid suspension. (3) Add tridecafluorooctyltriethoxysilane to the ternary hybrid suspension, adjust the pH to 4-5.5, raise the temperature to 50-70℃, stir the reaction for 1.5-3h to obtain the product; separate the solid and liquid of the product, dry it, and pulverize it to obtain the graphene-alumina silica-furan black in-situ hybrid intercalation filler.

[0008] The mass ratio of the graphene, sheet aluminum silicate, hydrophobic fumed silica and tridecafluorooctyltriethoxysilane is 1:(4-6):(1.5-2.5):(0.15-0.35).

[0009] By adopting the above technical solution, a hybrid filler is prepared by in-situ self-assembly process of liquid-phase ultrasonic synergistic stirring. Graphene is first dispersed into a few-layer state in an ethanol aqueous solution. Then, under the dual action of ultrasonic cavitation and mechanical stirring, sheet-like aluminum silicate is uniformly inserted into the spaces between the graphene sheets, and silica nanoparticles are simultaneously anchored in the gaps between the sheet overlaps.

[0010] Preferably, in step (1), graphene is added to an ethanol aqueous solution, ultrasonically dispersed, and 3-aminopropyltriethoxysilane is added and the pH is adjusted to 4-5.5. The mixture is stirred at 50°C for 30-60 min to obtain a dispersion. The amount of 3-aminopropyltriethoxysilane added is 5%-15% of the mass of graphene.

[0011] By adopting the above technical solution, 3-aminopropyltriethoxysilane is first introduced to pre-modify the surface of graphene with amino groups. The aminosilane is hydrolyzed under acidic catalysis to generate active silanol groups, which condense with residual oxygen-containing groups at the edge of graphene, thus pre-implanting active amino sites on the graphene surface. The introduction of amino groups produces two synergistic effects: first, protonation makes the graphene surface positively charged, enhancing its electrostatic attraction with negatively charged aluminum silicate and silica, thereby improving the efficiency of subsequent intercalation assembly; second, it provides hydrogen bonds and acid-base interaction anchors for the silanol groups of subsequent fluorosilanes, thereby improving the interfacial bonding strength between graphene, aluminum silicate and silica.

[0012] Preferably, in step (3), tridecafluorooctyltriethoxysilane is added to the ternary hybrid suspension, the pH is adjusted to 4-5.5, the temperature is raised to 50-70℃ in a closed environment, and the reaction is stirred for 1.5-3h to obtain the product; the product is separated into solid and liquid, dried and pulverized to obtain the graphene-alumina silica-furan black in-situ hybrid intercalation filler.

[0013] By adopting the above technical solution, in the fluorosilane grafting modification stage, a closed reactor is used and maintained under a micro-positive pressure of 0.12-0.2 MPa and acidic catalysis conditions of 50-70℃ (pH 4-5.5). The closed environment prevents solvent evaporation, maintains the liquid-phase reaction system, and ensures sufficient contact of silane at the interface of graphene, aluminum silicate, and silica. Acidic catalysis accelerates the hydrolysis of silane to generate active silanol groups, which efficiently condense with the surface hydroxyl groups of each component to form Si-O-Si covalent bonds. Compared with conventional physical adsorption modification by atmospheric pressure stirring, the covalent anchoring strength is improved under the closed micro-positive pressure acidic catalytic environment, allowing the structure of the hybrid filler to be stably maintained during subsequent high-shear mixing and processing, without being dissociated or destroyed.

[0014] Preferably, the method for preparing the sheet-like aluminum silicate includes the following steps: Aluminum sulfate or aluminum chloride is dissolved in deionized water to prepare an aluminum salt solution with a concentration of 0.3-0.8 mol / L; sodium silicate is dissolved in deionized water to prepare a silicon source solution with a concentration of 0.5-1.5 mol / L; the silicon source solution and aluminum salt solution are added dropwise simultaneously and in parallel under stirring in a water bath at 60-80℃. After the addition is complete, urea is added, and stirring is continued for 30-60 min. The pH is then adjusted to 8-9.5 to form a silica-alumina composite gel; the silica-alumina composite gel is subjected to a hydrothermal reaction at 180-220℃ for 12-24 h to obtain the product; the product is washed and dried to obtain a dried material; the dried material is heated to 600-750℃ at a rate of 2-5℃ / min, kept at that temperature for 2-4 h, and then naturally cooled to room temperature to obtain the sheet-like aluminum silicate.

[0015] By employing the above-mentioned technical solution, a silicon-aluminum composite gel precursor is prepared using a simultaneous co-dropping method with aluminum and silicon sources. Compared to conventional unidirectional drop-feeding processes, this method maintains a constant aluminum-silicon ratio throughout the process, avoiding the formation of impurity phases and uneven sheet thickness caused by local component imbalances. Subsequent hydrothermal crystallization at 180-220℃ promotes two-dimensional oriented growth, followed by medium-temperature calcination at 600-750℃ for shaping. The calcination temperature is intentionally controlled below 750℃, lower than the conventional high-temperature treatment of aluminum silicate powder (above 900℃), to retain the abundant active hydroxyl groups on the sheet surface. These active hydroxyl groups can form a dense hydrogen bond network with graphene oxygen-containing groups and silica during subsequent liquid-phase assembly, and provide numerous covalent grafting sites for fluorosilanes, forming the basis for constructing a three-phase chemically integrated hybrid filler.

[0016] Preferably, in the method for preparing the sheet-like aluminum silicate, hexadecyltrimethylammonium bromide is added simultaneously with urea.

[0017] By employing the above technical solution, cetyltrimethylammonium bromide (CTAB) is introduced as a morphology-directing agent during the preparation stage of the silica-alumina composite gel. Its cations selectively adsorb onto specific crystal planes of the precursor, while the long-chain alkyl groups form steric hindrance, inhibiting material deposition along these crystal planes and forcing the crystals to preferentially grow along the unadsorbed crystal planes in two dimensions, resulting in ultrathin sheet-like aluminum silicate. CTAB is completely thermally decomposed and removed during the subsequent calcination stage at 600-750℃, leaving no residue and not affecting the purity of the aluminum silicate. The ultrathin sheet layer possesses a larger aspect ratio and specific surface area, providing a larger insulating and isolating area for graphene with the same amount of CTAB. The constructed labyrinthine barrier network is more compact, while also providing more hydroxyl grafting sites, comprehensively enhancing the insulating and chemical anchoring effects of the hybrid filler.

[0018] Preferably, the halogen-free compound flame retardant filler is a mixture of aluminum hydroxide, zinc borate and phosphate glass in a mass ratio of (4-6):(1-3):(2-4), and is modified with tridecafluorooctyltriethoxysilane.

[0019] By employing the above technical solution, aluminum hydroxide decomposes and absorbs heat to release water vapor, zinc borate melts to form a viscous glassy coating layer, and phosphate glass powder further melts and spreads to form a dense ceramic shell. Simultaneously, the gradient temperature synergy mechanism of these three components ensures the sheath maintains structural integrity under continuous flame exposure. Fluorosilane surface modification reduces the surface energy of the flame-retardant filler, improving its compatibility with the fluorosilicone rubber matrix, while simultaneously forming a homogeneous interface layer with the fluorocarbon chains on the surface of the hybrid filler, reducing microscopic defects between the filler and the matrix.

[0020] Secondly, this application provides a method for preparing a fluorosilicone rubber fire-resistant cable sheath, using the following technical solution: A method for preparing a fluorosilicone rubber fire-resistant cable sheath includes the following steps: S1. Mix activated magnesium oxide, graphene-aluminum silicate-silica in-situ hybrid intercalation filler and halogen-free composite flame retardant filler at a rotor linear velocity of 20-35 m / s for 10-15 min to obtain composite filler. S2, plasticize the fluorosilicone raw rubber at 60-75℃ for 3-5 minutes, add composite filler and fluorosilicone oil, and continue to mix for 8-12 minutes, controlling the mixing temperature to ≤90℃ during the process, to obtain the rubber compound; S3, after the rubber compound cools down to below 50℃, add the bis(2,5) vulcanizing agent and TAIC crosslinking agent, and mix for 3-4 minutes to obtain the mixture; S4. The mixture is fed into a two-roll open mill for thin passing 5-8 times at a roller temperature of 40-60℃. After pressing, it is allowed to stand at room temperature for 16-24 hours to obtain the film. S5. The film is extruded and wrapped onto the cable core wire. After wrapping, it is first continuously vulcanized at 170-180℃ for 6-12 minutes, and then vulcanized at 185℃ for 4-5 hours. After cooling and winding, the fluorosilicone rubber fireproof cable sheath is obtained.

[0021] By adopting the above technical solutions, the S1 premixing stage utilizes high-speed mixing to pre-form active magnesium oxide, hybrid fillers, and flame-retardant fillers into a uniform composite powder, reducing the powder load in the internal mixing stage; the S2 internal mixing stage controls the upper limit of temperature to 90℃ to prevent early scorching of the fluorosilicone raw rubber before vulcanization; the S3 low-temperature vulcanization ensures that the vulcanizing agent and crosslinking agent are uniformly dispersed at a safe temperature; the S4-S5 extrusion and segmented vulcanization processes work together to ensure that the sheath achieves sufficient crosslinking and stable dimensional accuracy during the molding process.

[0022] Preferably, in S2, the fluorosilicone raw rubber is plasticized at 60-75℃ for 3-5 minutes, and the composite filler is added in 2-4 batches, with each batch added and then mixed for 1-2 minutes; then fluorosilicone oil is added and mixing continues, with a total mixing time of 8-12 minutes, during which the temperature of the mixing chamber is controlled to be ≤90℃, to obtain the rubber compound.

[0023] By adopting the above technical solution, during the intensive mixing stage, the composite filler is preferentially absorbed and dispersed in the high-viscosity raw rubber. Strong shear force is used to achieve uniform distribution of the filler in the matrix and dissociation of agglomerates. After dispersion, fluorosilicone oil is used to reduce the overall viscosity, improving subsequent extrusion flowability and product surface quality. This step-by-step feeding sequence avoids the problems of insufficient powder absorption and dispersion caused by premature lubrication with fluorosilicone oil. It ensures that the microscopic isolation structure of the hybrid intercalated filler is completely preserved throughout the mixing process, resulting in final products exhibiting excellent insulation, mechanical properties, and surface quality.

[0024] Preferably, in S5, the temperature control of each section of the extruder is as follows: feeding section 50-60℃, compression section 65-75℃, metering section 75-85℃, and die head 80-90℃.

[0025] In summary, this application has the following beneficial effects: 1. This application constructs an integrated hybrid filler structure that "physically isolates graphene with aluminum silicate sheets and fills the gaps between the sheets with silica particles," thereby blocking the conductive path of graphene from the source. At the same time, the labyrinthine barrier network formed by the staggered arrangement of two-dimensional sheets extends the electrolyte penetration path and works synergistically with halogen-free compound flame-retardant fillers to form carbon, thus simultaneously improving the insulation, electrolyte resistance, and flame retardancy of the sheath.

[0026] 2. This application pre-modifies the surface of graphene with amino groups using 3-aminopropyltriethoxysilane, pre-implanting active amino sites on the graphene surface. The electrostatic attraction between protonated amino groups and negatively charged inorganic particles enhances the intercalation assembly efficiency and provides hydrogen bond and acid-base interaction anchors for subsequent fluorosilanes, thereby strengthening the chemical bonding strength of the three-phase interface.

[0027] 3. In the preparation stage of the silicon-aluminum composite gel, this application introduces hexadecyltrimethylammonium bromide as a morphology guiding agent. It utilizes the selective crystal plane adsorption and steric hindrance effect to induce the two-dimensional preferential growth of crystals, promotes the reduction of sheet thickness and the increase of aspect ratio. After calcination, CTAB is completely removed without residue. After the sheet is thinned, the isolation area for graphene and the density of hydroxyl grafting sites are increased, which is beneficial to strengthening the insulation isolation and interface anchoring effect of the hybrid filler. Detailed Implementation

[0028] The present application will be further described in detail below with reference to the embodiments.

[0029] Unless otherwise specified, the raw materials used in the preparation examples, embodiments, and comparative examples of this application are all commercially available.

[0030] Preparation Examples 1-4: Sheet-shaped aluminum silicate Preparation Example 1 This preparation example discloses a method for preparing sheet-like aluminum silicate, specifically including the following steps: Step 1: Weigh 66.6g of aluminum sulfate (Al2(SO4)3·18H2O, 0.1mol) and dissolve it in 200mL of deionized water, stirring until completely dissolved to prepare an aluminum salt solution with a concentration of 0.5mol / L; weigh 71.0g of sodium silicate (Na2SiO3·9H2O, 0.25mol) and dissolve it in 200mL of deionized water to prepare a silicon source solution with a concentration of 1.25mol / L; the aluminum-silicon molar ratio is 1:2.5. Step 2: Under the conditions of a 70℃ water bath and 400rpm mechanical stirring, the aluminum salt solution and silicon source solution were simultaneously and concurrently added to a 500mL three-necked flask through a constant pressure dropping funnel at a dropping rate of 3mL / min. After the addition was complete, 30g of urea (0.5mol) was added, and stirring was continued for 45min. Dilute ammonia (10wt%) was added dropwise to adjust the pH of the system to 8.5, and stirring was continued for 15min to form a silicon-aluminum composite gel. Step 3: Transfer the gel to a 1L polytetrafluoroethylene-lined high-pressure reactor, seal it, and place it in an oven. Heat the reactor to 200℃ at a rate of 2℃ / min and maintain the temperature for 18 hours for hydrothermal reaction. After the reaction, allow it to cool naturally to room temperature. Wash the hydrothermal product with deionized water by centrifugation (4000rpm × 10min / time). Measure the conductivity of the supernatant after each wash. Repeat the washing until the conductivity drops below 20μS / cm and the decrease in conductivity between two consecutive washes does not exceed 10%. Then wash twice with anhydrous ethanol. After filtration, place the filter cake in an oven and dry it at 105℃ for 18 hours to obtain the precursor powder. Step 4: Place the precursor powder in a muffle furnace, heat it to 675°C at a rate of 3°C / min, hold it at that temperature for 3 hours, let it cool naturally to room temperature with the furnace, grind it through a 300-mesh sieve, and you will get flake aluminum silicate.

[0031] Preparation Example 2 This preparation example is basically the same as Preparation Example 1, except that in step 2, under the conditions of a 70°C water bath and 400 rpm mechanical stirring, the aluminum salt solution and the silicon source solution are simultaneously and concurrently added to a 500 mL three-necked flask through a constant pressure dropping funnel at a dropping rate of 3 mL / min. After the addition is complete, 30 g of urea (0.5 mol) and 2.4 g of hexadecyltrimethylammonium bromide (CTAB, accounting for about 2% of the total mass of silicon and aluminum oxide) are added, and stirring is continued for 45 min. Dilute ammonia water (concentration 10 wt%) is added dropwise to adjust the pH of the system to 8.5, and stirring is continued for 15 min to form a silicon-aluminum composite gel.

[0032] Preparation Example 3 This preparation example discloses a method for preparing sheet-like aluminum silicate, specifically including the following steps: Step 1: Weigh 66.6g of aluminum sulfate (Al2(SO4)3·18H2O, 0.1mol) and dissolve it in 333mL of deionized water. Stir until completely dissolved to prepare an aluminum salt solution with a concentration of 0.3mol / L. Weigh 28.4g of sodium silicate (Na2SiO3·9H2O, 0.1mol) and dissolve it in 200mL of deionized water to prepare a silicon source solution with a concentration of 0.5mol / L. The aluminum-silicon molar ratio is 1:1. Step 2: Under the conditions of a 60℃ water bath and 300rpm mechanical stirring, the aluminum salt solution and silicon source solution were simultaneously and concurrently added dropwise to a 500mL three-necked flask through a constant pressure dropping funnel at a dropping rate of 2mL / min. After the addition was complete, 18g of urea (0.3mol) and 1g of hexadecyltrimethylammonium bromide (CTAB, accounting for about 1% of the total mass of silicon and aluminum oxide) were added, and stirring was continued for 30min. Dilute ammonia water (10wt%) was added dropwise to adjust the pH of the system to 8, and stirring was continued for 15min to form a silicon-aluminum composite gel. Step 3: Transfer the gel to a 1L polytetrafluoroethylene-lined high-pressure reactor, seal it, and place it in an oven. Heat the reactor to 180℃ at a rate of 2℃ / min and maintain the temperature for 24 hours for hydrothermal reaction. After the reaction, allow it to cool naturally to room temperature. Wash the hydrothermal product with deionized water by centrifugation (4000rpm×10min / time). Measure the conductivity of the supernatant after each wash. Repeat the washing until the conductivity drops below 20μS / cm and the decrease in conductivity between two consecutive washes does not exceed 10%. Then wash twice with anhydrous ethanol. After filtration, place the filter cake in an oven and dry it at 105℃ for 24 hours to obtain the precursor powder. Step 4: Place the precursor powder in a muffle furnace, heat it to 600°C at a rate of 2°C / min, hold it at that temperature for 4 hours, let it cool naturally to room temperature with the furnace, grind it through a 300-mesh sieve, and you will get flake aluminum silicate.

[0033] Preparation Example 4 This preparation example discloses a method for preparing sheet-like aluminum silicate, specifically including the following steps: Step 1: Weigh 66.6g of aluminum sulfate (Al2(SO4)3·18H2O, 0.1mol) and dissolve it in 125mL of deionized water, stirring until completely dissolved to prepare an aluminum salt solution with a concentration of 0.8mol / L; weigh 71g of sodium silicate (Na2SiO3·9H2O, 0.25mol) and dissolve it in 47mL of deionized water to prepare a silicon source solution with a concentration of 1.5mol / L; the aluminum-silicon molar ratio is 1:2.5. Step 2: Under conditions of an 80℃ water bath and mechanical stirring at 800rpm, the aluminum salt solution and silicon source solution were simultaneously and concurrently added dropwise to a 500mL three-necked flask through a constant pressure dropping funnel at a dropping rate of 4mL / min. After the addition was complete, 60g of urea (1mol) and 4.1g of hexadecyltrimethylammonium bromide (CTAB, accounting for approximately 3% of the total mass of the silicon-aluminum oxide) were added, and stirring was continued for 60min. Dilute ammonia (10wt%) was added dropwise to adjust the pH of the system to 9.5, and stirring was continued for 15min to form a silicon-aluminum composite gel. Step 3: Transfer the gel to a 1L polytetrafluoroethylene-lined high-pressure reactor, seal it, and place it in an oven. Heat the reactor to 210℃ at a rate of 2℃ / min and maintain the temperature for 12 hours for hydrothermal reaction. After the reaction, allow it to cool naturally to room temperature. Wash the hydrothermal product with deionized water by centrifugation (4000rpm × 10min / time). Measure the conductivity of the supernatant after each wash. Repeat the washing until the conductivity drops below 20μS / cm and the decrease in conductivity between two consecutive washes does not exceed 10%. Then wash twice with anhydrous ethanol. After filtration, place the filter cake in an oven and dry it at 110℃ for 12 hours to obtain the precursor powder. Step 4: Place the precursor powder in a muffle furnace, heat it to 750°C at a rate of 5°C / min, hold it at that temperature for 2 hours, let it cool naturally to room temperature with the furnace, grind it through a 300-mesh sieve, and you will get flake aluminum silicate.

[0034] Preparation Examples 5-10: In-situ Hybrid Intercalated Fillers of Graphene-Alumina Silicate-Silica Preparation Example 5 This preparation example discloses a method for preparing an in-situ hybrid intercalated filler of graphene-alumina silicate-fumed silica, which specifically includes the following steps: (1) Weigh 2.0g of graphene powder, add it to 400mL of ethanol aqueous solution (the volume ratio of anhydrous ethanol to deionized water is 3.5:1), place it in an ultrasonic cleaner, and disperse it for 45min under ultrasonic power of 350W to obtain graphene dispersion. (2) Add 10.0g of sheet aluminum silicate (obtained from Preparation Example 1) and 4.0g of hydrophobic fumed silica to the graphene dispersion obtained in step (1), place it in an ultrasonic cleaner, ultrasonic power 350W, mechanical stirring speed 500rpm, and synergistically treat for 3h to obtain a ternary hybrid suspension. (3) Add 0.50 g of tridecafluorooctyltriethoxysilane (approximately 3.1 wt% of the total mass of graphene, aluminum silicate, and silica in the hybrid filler, which is 16.0 g) to the ternary hybrid suspension obtained in step (2), adjust the pH of the system to 4.8 with dilute acetic acid, raise the temperature to 60°C, and stir the reaction for 2 h; after the reaction is completed, let it stand and cool to room temperature; (4) The reaction product obtained in step (3) is vacuum filtered, the filter cake is washed twice with anhydrous ethanol and dried in an oven at 80°C for 12 hours; the dried product is pulverized by a high-speed pulverizer and passed through a 200-mesh sieve to obtain the graphene-alumina silicate-silica in-situ hybrid intercalation filler.

[0035] Preparation Example 6 This preparation example is basically the same as preparation example 5, except that in step (1), 2.0 g of graphene powder is weighed and added to 400 mL of ethanol aqueous solution (the volume ratio of anhydrous ethanol to deionized water is 3.5:1), and ultrasonically dispersed for 30 min; 0.20 g of 3-aminopropyltriethoxysilane (APTES, accounting for 10% of the mass of graphene) is added to the dispersion, the pH is adjusted to 4.5 with dilute acetic acid, the temperature is raised to 50 °C, and the reaction is stirred for 45 min to obtain the graphene dispersion.

[0036] Preparation Example 7 This preparation example is basically the same as Preparation Example 5, except that in step (3), the ternary hybrid suspension obtained in step (2) is transferred to a closed reaction vessel, 0.50 g of tridecafluorooctyltriethoxysilane (accounting for about 3.1 wt% of the total mass of graphene, aluminum silicate and silica in the hybrid filler of 16.0 g) is added, the pH is adjusted to 4.5 with dilute acetic acid, the temperature is raised to 60 °C, the absolute pressure inside the vessel is about 0.15 MPa and maintained stable, and the reaction is stirred for 2 h; after the reaction is completed, it is allowed to stand and cool to room temperature.

[0037] Preparation Example 8 This preparation example is basically the same as preparation example 5, except that the sheet aluminum silicate in step (2) is obtained from preparation example 2.

[0038] Preparation Example 9 This preparation example discloses a method for preparing an in-situ hybrid intercalated filler of graphene-alumina silicate-fumed silica, which specifically includes the following steps: (1) Weigh 2.0g of graphene powder and add it to 400mL of ethanol aqueous solution (the volume ratio of anhydrous ethanol to deionized water is 3:1). Disperse the solution by ultrasonication for 30min. Add 0.10g of 3-aminopropyltriethoxysilane (APTES, accounting for 5% of the mass of graphene) to the dispersion, adjust the pH to 4.5 with dilute acetic acid, heat to 50℃, and stir for 30min to obtain graphene dispersion. (2) Add 8.0g of sheet aluminum silicate (obtained from Preparation Example 3) and 3.0g of hydrophobic fumed silica to the graphene dispersion obtained in step (1), place it in an ultrasonic cleaner, ultrasonic power 200W, mechanical stirring speed 300rpm, and synergistic treatment for 2h to obtain a ternary hybrid suspension. (3) Transfer the ternary hybrid suspension obtained in step (2) to a closed reaction vessel, add 0.30 g of tridecafluorooctyltriethoxysilane (accounting for about 2.3 wt% of the total mass of graphene, aluminum silicate and silica in the hybrid packing material of 13.0 g), adjust the pH to 4.0 with dilute acetic acid, raise the temperature to 50°C, maintain the absolute pressure in the vessel at about 0.12 MPa, and stir the reaction for 1.5 h; after the reaction is completed, let it stand and cool to room temperature; (4) The reaction product obtained in step (3) is vacuum filtered, the filter cake is washed twice with anhydrous ethanol and dried in an oven at 80°C for 12 hours; the dried product is pulverized by a high-speed pulverizer and passed through a 200-mesh sieve to obtain the graphene-alumina silicate-silica in-situ hybrid intercalation filler.

[0039] Preparation Example 10 This preparation example discloses a method for preparing an in-situ hybrid intercalated filler of graphene-alumina silicate-fumed silica, which specifically includes the following steps: (1) Weigh 2.0g of graphene powder and add it to 400mL of ethanol aqueous solution (the volume ratio of anhydrous ethanol to deionized water is 4:1). Disperse the solution by ultrasonication for 30min. Add 0.30g of 3-aminopropyltriethoxysilane (APTES, accounting for 15% of the mass of graphene) to the dispersion, adjust the pH to 5.5 with dilute acetic acid, heat to 50℃, and stir for 60min to obtain graphene dispersion. (2) Add 12.0g of sheet aluminum silicate (obtained from Preparation Example 4) and 5.0g of hydrophobic fumed silica to the graphene dispersion obtained in step (1), place it in an ultrasonic cleaner, ultrasonic power 500W, mechanical stirring speed 800rpm, and synergistically treat for 4h to obtain a ternary hybrid suspension. (3) Transfer the ternary hybrid suspension obtained in step (2) to a closed reaction vessel, add 0.70 g of tridecafluorooctyltriethoxysilane (accounting for about 3.7 wt% of the total mass of graphene, aluminum silicate and silica in the hybrid packing material of 13.0 g), adjust the pH to 5.5 with dilute acetic acid, raise the temperature to 70°C, maintain the absolute pressure in the vessel at about 0.20 MPa, and stir the reaction for 3 h; after the reaction is completed, let it stand and cool to room temperature; (4) The reaction product obtained in step (3) is vacuum filtered, the filter cake is washed twice with anhydrous ethanol and dried in an oven at 80°C for 12 hours; the dried product is pulverized by a high-speed pulverizer and passed through a 200-mesh sieve to obtain the graphene-alumina silicate-silica in-situ hybrid intercalation filler.

[0040] Example 1 This embodiment provides a method for preparing a fluorosilicone rubber fire-resistant cable sheath, including the following steps: S0, 85g of aluminum hydroxide, 34g of zinc borate, and 51g of phosphate glass powder (mass ratio of 5:2:3) were added to a high-speed mixer and mixed for 5 minutes at a rotor linear speed of 20m / s to obtain a compound powder. The compound powder was added to 500mL of ethanol aqueous solution (volume ratio of anhydrous ethanol to deionized water 3.5:1) and stirred to disperse evenly. 3.4g of tridecafluorooctyltriethoxysilane (accounting for 2wt% of the total mass of flame retardant filler) was added, and the pH of the system was adjusted to 4.5 with dilute acetic acid. The temperature was raised to 60℃ and stirred for 1.5h. After the reaction was completed, the mixture was filtered, the filter cake was washed twice with anhydrous ethanol, dried at 80℃ for 6h, and ground through a 200-mesh sieve to obtain a halogen-free compound flame retardant filler with hydrophobic surface treatment by tridecafluorooctyltriethoxysilane. S1, 20g of activated magnesium oxide, 25g of graphene-alumina silicate-silica in-situ hybrid intercalation filler (obtained from Preparation Example 5) and halogen-free composite flame retardant filler were put into a high-speed mixer and mixed for 12min at a rotor linear speed of 28m / s to obtain composite filler. S2, 1000g of fluorosilicone raw rubber (peroxide-curable type, vinyl molar content 0.15%~0.5%) is added to an internal mixer and plasticized at 68℃ for 4min; the composite filler obtained in step S1 is divided into 3 equal batches and added to the internal mixer, and each batch is mixed for 1.5min after addition; after all the powder is added, 9g of fluorosilicone oil is added, and mixing continues until the total time reaches 10min, during which the temperature of the mixing chamber is controlled at 75~88℃, and the rubber compound is obtained by discharge; S3. Place the rubber compound obtained in step S2 on a two-roll mill and cool it to 45°C; add 8g of 2-5 vulcanizing agent and 12g of TAIC crosslinking agent, mix for 3.5 minutes, and knead in a triangular shape 4 times to obtain the mixture. S4. The mixture obtained in step S3 is passed through a two-roll mill 6 times at a roller temperature of 50°C. The roller gap is adjusted to press it into a 3.5mm thick sheet, which is then left to stand and mature at room temperature for 20 hours. S5. The cured rubber sheet from step S4 is filtered through a rubber filter (100-mesh screen) and fed into an extruder to coat the cable core. The extruder temperature settings are as follows: feeding section 55℃, compression section 70℃, metering section 80℃, and die head 85℃. After coating, it undergoes a first-stage continuous vulcanization at 170℃ for 9 minutes, followed by a second-stage vulcanization at 185℃ for 4.5 hours. After cooling and winding, a fluorosilicone rubber fireproof cable sheath is obtained.

[0041] Example 2 This embodiment is basically the same as that of Example 1, except that: in S1, the graphene-alumina silicate-fumed silica in-situ hybrid intercalation filler is the one obtained in Preparation Example 6.

[0042] Example 3 This embodiment is basically the same as that of Example 1, except that: in S1, the graphene-alumina silicate-fumed silica in-situ hybrid intercalation filler is the one obtained in Preparation Example 7.

[0043] Example 4 This embodiment is basically the same as Example 1, except that: in S1, the graphene-alumina silicate-fumed silica in-situ hybrid intercalation filler is the one obtained in Preparation Example 8.

[0044] Example 5 This embodiment provides a method for preparing a fluorosilicone rubber fire-resistant cable sheath, including the following steps: S0, 68.6g of aluminum hydroxide, 17.1g of zinc borate, and 34.3g of phosphate glass powder (mass ratio of 4:1:2) were added to a high-speed mixer and mixed for 5 minutes at a rotor linear speed of 20m / s to obtain a compound powder. The compound powder was added to 400mL of ethanol aqueous solution (volume ratio of anhydrous ethanol to deionized water 3:1) and stirred to disperse evenly. 1.8g of tridecafluorooctyltriethoxysilane (accounting for 1.5wt% of the total mass of the flame retardant filler) was added, and the pH of the system was adjusted to 4.5 with dilute acetic acid. The temperature was raised to 55℃ and stirred for 1 hour. After the reaction was completed, the mixture was filtered, the filter cake was washed twice with anhydrous ethanol, dried at 80℃ for 6 hours, and ground through a 200-mesh sieve to obtain a halogen-free compound flame retardant filler with a hydrophobic surface treatment of tridecafluorooctyltriethoxysilane. S1, 10g of active magnesium oxide, 10g of graphene-alumina silicate-silica in-situ hybrid intercalation filler (obtained from Preparation Example 9), and halogen-free composite flame retardant filler were put into a high-speed mixer and mixed for 15min at a rotor linear speed of 20m / s to obtain composite filler. S2, 1000g of fluorosilicone raw rubber (peroxide-curable type, vinyl molar content 0.15%~0.5%) is added to an internal mixer and plasticized at 60℃ for 5min; the composite filler obtained in step S1 is divided into 4 equal batches and added to the internal mixer, and each batch is mixed for 2min after addition; after all the powder is added, 6g of fluorosilicone oil is added, and mixing continues until the total time reaches 12min, during which the temperature of the mixing chamber is controlled at 60~82℃, and the rubber compound is obtained by discharge; S3. Place the rubber compound obtained in step S2 on a two-roll mill and cool it to 40°C. Add 4g of 2-5 vulcanizing agent and 8g of TAIC crosslinking agent, mix for 3 minutes, and knead in a triangular shape 3 times to obtain the mixture. S4. The mixture obtained in step S3 is passed through a two-roll mill 5 times at a roller temperature of 40°C. The roller gap is adjusted and the mixture is pressed into a 3mm thick sheet. The sheet is then left to stand and mature at room temperature for 16 hours. S5. The cured rubber sheet from step S4 is filtered through a rubber filter (80-mesh screen) and fed into an extruder to coat the cable core. The extruder temperature settings are as follows: feeding section 50℃, compression section 65℃, metering section 75℃, and die head 80℃. After coating, it undergoes continuous vulcanization at 170℃ for 12 minutes, followed by vulcanization at 185℃ for 5 hours. After cooling and winding, a fluorosilicone rubber fireproof cable sheath is obtained.

[0045] Example 6 This embodiment provides a method for preparing a fluorosilicone rubber fire-resistant cable sheath, including the following steps: S0, 101.5g of aluminum hydroxide, 50.8g of zinc borate, and 67.7g of phosphate glass powder (mass ratio of 6:3:4) were added to a high-speed mixer and mixed for 5 minutes at a rotor linear speed of 20m / s to obtain a compound powder. The compound powder was added to 600mL of ethanol aqueous solution (volume ratio of anhydrous ethanol to deionized water 4:1) and stirred to disperse evenly. 6.6g of tridecafluorooctyltriethoxysilane (accounting for 3wt% of the total mass of the flame retardant filler) was added, and the pH of the system was adjusted to 4.5 with dilute acetic acid. The temperature was raised to 65℃ and stirred for 2 hours. After the reaction was completed, the mixture was filtered, the filter cake was washed twice with anhydrous ethanol, dried at 80℃ for 6 hours, and ground through a 200-mesh sieve to obtain a halogen-free compound flame retardant filler with a hydrophobic surface treatment of tridecafluorooctyltriethoxysilane. S1. 30g of active magnesium oxide, 40g of graphene-alumina silicate-silica in-situ hybrid intercalation filler (obtained from Preparation Example 10) and halogen-free composite flame retardant filler were put into a high-speed mixer and mixed for 10min at a rotor linear speed of 35m / s to obtain composite filler. S2, 1000g of fluorosilicone raw rubber (peroxide-curable type, vinyl molar content 0.15%~0.5%) is added to an internal mixer and plasticized at 75℃ for 3 minutes; the composite filler obtained in step S1 is divided into 3 equal batches and added to the internal mixer, and each batch is mixed for 1 minute after addition; after all the powder is added, 12g of fluorosilicone oil is added, and mixing continues until the total time reaches 8 minutes, during which the temperature of the mixing chamber is controlled at 78~90℃, and the rubber compound is obtained by discharge; S3. Place the rubber compound obtained in step S2 on a two-roll mill and cool it to 48°C. Add 12g of 2-5 vulcanizing agent and 16g of TAIC crosslinking agent, mix for 4 minutes, and knead in a triangular shape 5 times to obtain the mixture. S4. The mixture obtained in step S3 is passed through a two-roll mill 8 times at a roller temperature of 60°C. The roller gap is adjusted and the mixture is pressed into a 4mm thick sheet. The sheet is then left to stand and mature at room temperature for 20 hours. S5. The cured rubber sheet from step S4 is filtered through a rubber filter (120-mesh screen) and fed into an extruder to coat the cable core. The extruder temperature settings are as follows: feeding section 60℃, compression section 75℃, metering section 85℃, and die head 90℃. After coating, it undergoes a first-stage continuous vulcanization at 180℃ for 6 minutes, followed by a second-stage vulcanization at 185℃ for 4 hours. After cooling and winding, a fluorosilicone rubber fireproof cable sheath is obtained.

[0046] Comparative Example 1 The difference between this comparative example and Example 1 is that the graphene-alumina silicate-fumed silica in-situ hybrid intercalation filler is replaced with an equal amount of graphene.

[0047] Comparative Example 2 The difference between this comparative example and Example 1 is that the in-situ hybrid intercalation filler of graphene-alumina silica-furan black is replaced with 18.75g of graphene-alumina silica binary hybrid intercalation filler and 6.25g of hydrophobic furan black produced by vapor phase method. The preparation method of the graphene-alumina silica binary hybrid intercalation filler is as follows: 2.0g of graphene powder is weighed and added to 400mL of ethanol aqueous solution (anhydrous ethanol to deionized water volume ratio 3.5:1), placed in an ultrasonic cleaner, and dispersed for 45min at an ultrasonic power of 350W to obtain a graphene dispersion; 10.0g of sheet-like aluminum silicate (obtained from Preparation Example 1) is added to the graphene dispersion and placed in an ultrasonic cleaner. In a washing apparatus, ultrasonic power of 350W and mechanical stirring speed of 500rpm were used for synergistic treatment for 3h to obtain a binary hybrid suspension. 0.37g of tridecafluorooctyltriethoxysilane (accounting for about 3.1wt% of the total mass of graphene and aluminum silicate in the hybrid filler of 12.0g) was added to the binary hybrid suspension, the pH of the system was adjusted to 4.8 with dilute acetic acid, the temperature was raised to 60℃, and the reaction was stirred for 2h. After the reaction was completed, it was allowed to stand and cool to room temperature. The reaction product was vacuum filtered, the filter cake was washed twice with anhydrous ethanol, and dried in an oven at 80℃ for 12h. The dried product was pulverized with a high-speed pulverizer and passed through a 200-mesh sieve to obtain the graphene-alumina silicate in-situ hybrid intercalation filler.

[0048] Performance testing The thickness of the sheet-like aluminum silicate obtained in Examples 1-4 was tested using a scanning electron microscope. A small amount of powder sample was ultrasonically dispersed in anhydrous ethanol, dropped onto the silicon wafer surface and dried, and then placed under a scanning electron microscope to observe the sheet morphology. The sheet thickness was measured by selecting a representative field of view, and the test results are recorded in Table 1.

[0049] The flake size of the aluminum silicate obtained in Preparation Examples 1-4 was determined by wet dispersion using a laser particle size analyzer. The powder sample was added to deionized water, ultrasonically dispersed, and then injected into the sample cell. The median particle size was expressed as D50. The test results are recorded in Table 1.

[0050] The specific surface area of ​​the flake aluminum silicate obtained in Preparation Examples 1-4 was determined by the BET nitrogen adsorption method. After the powder samples were pretreated by vacuum degassing at 150℃, nitrogen adsorption-desorption isotherm tests were performed at liquid nitrogen temperature. The specific surface area was calculated by the BET equation. The test results are shown in Table 1.

[0051] The volume resistivity of the graphene-alumina silicate-fumed silica in-situ hybrid intercalated fillers obtained in Examples 5-10 and the graphene-alumina silicate binary hybrid intercalated fillers obtained in Comparative Example 2 was tested using a powder resistivity tester. An appropriate amount of powder was placed into a test mold and pressed into a sheet under a specified pressure. The volume resistivity was measured, and the test results are shown in Table 2.

[0052] The apparent density and tap density of the graphene-alumina silicate-fumed silica in-situ hybrid intercalated filler obtained in Examples 5-10 and the graphene-alumina silicate binary hybrid intercalated filler obtained in Comparative Example 2 were determined by the graduated cylinder tapping method. The powder was loaded into a weighed graduated cylinder, the initial volume and mass were recorded, and the apparent density was calculated. After tapping until the volume no longer changed, the tap density was calculated. The test results are shown in Table 2.

[0053] The fluorosilicone rubber fireproof cable sheaths obtained in Examples 1-6 and Comparative Examples 1-2 were tested as follows, and the test results are recorded in Table 3.

[0054] (1) Volume resistivity test: The vulcanized rubber sheets obtained in each example and comparative example were cut into circular samples with a diameter of 100 mm. The volume resistivity was tested using a high resistance meter at a DC voltage of 500 V according to GB / T 1410-2006. The test environment temperature was 23±2℃ and the relative humidity was 50±5%. Three samples were tested for each sample and the average value was taken.

[0055] (2) Dielectric breakdown strength test: The vulcanized rubber sheets obtained in each example and comparative example were cut into 100mm×100mm samples. The breakdown voltage tester was used to test the breakdown strength in transformer oil in accordance with GB / T 1408.1-2016 with a continuous voltage increase (voltage increase rate 2kV / s). The breakdown voltage value was recorded and divided by the sample thickness to obtain the breakdown strength. Five samples were tested for each sample and the average value was taken.

[0056] (3) Electrolyte immersion weight gain test: The vulcanized rubber sheets obtained in each example and comparative example were cut into 50mm×50mm samples, weighed, and then immersed in a sealed container containing a mixed solvent of ethylene carbonate / dimethyl carbonate / ethyl methyl carbonate. After being immersed at a constant temperature of 25℃ for 168h, the samples were taken out, the surface liquid was wiped dry, and the weight gain percentage was calculated. Three samples were tested for each sample and the average value was taken.

[0057] (4) Limiting oxygen index test: Cut the vulcanized rubber sheets obtained in each example and comparative example into strips of 150mm×6.5mm×3mm and test them with an oxygen index tester in accordance with GB / T 2406.2-2009. Adjust the mixing ratio of oxygen and nitrogen and record the minimum oxygen concentration required for the sample to maintain combustion for 3 minutes or a combustion length of 50mm. Test no less than 5 samples for each sample and take the average value.

[0058] (5) Tensile strength and elongation at break test: The vulcanized rubber sheets obtained in each example and comparative example were cut into standard specimens with a dumbbell-shaped cutter. The test was carried out using a universal electronic tensile testing machine in accordance with GB / T 528-2009. The tensile rate was 500 mm / min. The tensile strength and elongation at break were recorded. Five specimens were tested for each sample and the average value was taken.

[0059] (6) Test of volume resistivity retention rate after hot air aging: Cut the vulcanized rubber sheets obtained from each example and comparative example into 100mm×100mm samples, place them in a forced-air drying oven and age them in hot air at a constant temperature of 60℃ for 168h according to GB / T 3512-2014. After taking them out, place them under standard environmental conditions for 24h, and test the volume resistivity after aging according to the above volume resistivity test method, and calculate the retention rate relative to before aging.

[0060] Table 1 Performance test data of preparation examples 1-4

[0061] Table 2 Performance test data of Preparation Examples 5-10 and Comparative Example 2

[0062] Table 3 Performance test data of Examples 1-6 and Comparative Examples 1-2

[0063] As shown in Table 1, after introducing CTAB in Preparation Example 2, the sheet thickness was significantly reduced compared to Preparation Example 1 without CTAB, while the specific surface area increased accordingly. This is because CTAB, as a cationic surfactant, selectively adsorbs its hydrophilic end onto specific crystal planes of the aluminosilicate precursor through electrostatic interaction. The long-chain alkyl hydrophobic end forms a steric hindrance layer on the adsorbed crystal plane, inhibiting material deposition along that crystal plane direction. This forces the crystal to preferentially grow along the unadsorbed crystal plane in two dimensions, thereby obtaining a sheet structure with thinner thickness and a larger aspect ratio.

[0064] As shown in Table 2, the volume resistivity of the ternary hybrid fillers obtained in Examples 5-10 is all above 10¹. 0 The magnitude is on the order of Ω·cm or higher, far exceeding the 10 in Comparative Example 2. 7The values ​​are on the order of Ω·cm, indicating that the graphene sheets are effectively physically isolated by aluminum silicate, and the fumed silica particles fill and seal the gaps between the sheets, thus blocking the conductive pathways. In Preparation Example 6, the introduction of APTES to pre-modify the graphene with amino groups resulted in protonated amino groups that made the graphene surface positively charged, enhancing electrostatic attraction with the negatively charged aluminum silicate and fumed silica, improving intercalation assembly efficiency, and further increasing the powder volume resistivity compared to Preparation Example 5. In Preparation Example 7, the use of a closed-loop micro-positive pressure fluorosilane anchoring and an acidic catalytic environment accelerated the hydrolysis and condensation of fluorosilanes, forming more complete covalent bonds at the interface of the graphene, aluminum silicate, and fumed silica phases, resulting in a more stable insulating structure and increased powder volume resistivity. Comparative Example 2 used a binary hybrid filler; the fumed silica was not anchored in situ at the sheet overlap gaps during the liquid phase assembly stage, leaving residual conductive pathways between the graphene sheets and resulting in a significantly lower volume resistivity. The apparent density and tap density data indicate that the density of the ternary hybrid filler is lower than that of the binary hybrid filler in Comparative Example 2 due to its loose lamellar intercalation structure, which indirectly reflects the intercalation effect.

[0065] As shown in Table 3, the performance of Examples 1-6 is significantly better than that of Comparative Examples 1 and 2. Comparative Example 1 directly adds graphene without an insulating structure; the graphene sheets overlap to form conductive pathways, resulting in a volume resistivity and breakdown strength that are only about 0.35% and 52% of Example 1, respectively. Simultaneously, graphene agglomeration leads to discontinuous barrier networks, and the electrolyte weight gain is 2.5 times that of Example 1. Comparative Example 2 uses a binary hybrid filler mixed with silica via a dry process. The silica is not anchored in situ at the sheet overlap gaps during the liquid phase assembly stage, leaving residual conductive pathways between the graphene sheets. The volume resistivity decreases by approximately 75% compared to Example 1. Under strong shear during mixing, some silica detaches from the sheet surface, and the insulation retention rate after thermal aging significantly decreases from 78% in Example 1 to 58%. Example 2 introduced APTES amino pre-modification, Example 3 used closed micro-positive pressure fluorosilane anchoring, and Example 4 used CTAB-controlled thin-film aluminum silicate. The performance of each item was improved on the basis of Example 1. Among them, the closed micro-positive pressure covalent anchoring in Example 3 had the most significant improvement in insulation retention rate after thermal aging (93%), which directly proved the protective effect of chemical anchoring on the stability of hybrid structures during processing and aging.

Claims

1. A fluorosilicone rubber fireproof cable sheath, characterized in that, The raw materials include the following parts by weight: 100 parts of fluorosilicone raw rubber, 1-3 parts of activated magnesium oxide, 1-4 parts of graphene-alumina silica-furan black in-situ hybrid intercalation filler, 12-22 parts of halogen-free compound flame retardant filler, 0.6-1.2 parts of fluorosilicone oil, 0.4-1.2 parts of bis(2,5)sulfurizing agent and 0.8-1.6 parts of TAIC crosslinking agent; The preparation method of the graphene-alumina silicate-fumed silica in-situ hybrid intercalation filler is as follows: In an ethanol-water solution system, ultrasonic synergistic stirring is used to promote the intercalation of sheet-like alumina silicate into the spaces between graphene sheets, while hydrophobic vapor-phase fumed silica nanoparticles are simultaneously anchored at the gaps between the sheets. After being modified by fluorosilane grafting, the filler is dried and pulverized to obtain a ternary hybrid insulating barrier filler.

2. The fluorosilicone rubber fireproof cable sheath according to claim 1, characterized in that, The preparation method of the graphene-alumina silicate-fumed silica in-situ hybrid intercalation filler includes the following steps: (1) Add graphene to an aqueous ethanol solution and disperse it by ultrasonication to obtain a dispersion; (2) Add flake aluminum silicate and hydrophobic fumed silica to the dispersion, and treat for 2-4 hours at an ultrasonic power of 200-500W and a stirring rate of 300-800rpm to obtain a ternary hybrid suspension. (3) Add tridecafluorooctyltriethoxysilane to the ternary hybrid suspension, adjust the pH to 4-5.5, raise the temperature to 50-70℃, stir the reaction for 1.5-3h to obtain the product; separate the solid and liquid of the product, dry it, and pulverize it to obtain the graphene-alumina silica-furan black in-situ hybrid intercalation filler.

3. The fluorosilicone rubber fireproof cable sheath according to claim 2, characterized in that, The mass ratio of the graphene, sheet aluminum silicate, hydrophobic fumed silica and tridecafluorooctyltriethoxysilane is 1:(4-6):(1.5-2.5):(0.15-0.35).

4. The fluorosilicone rubber fireproof cable sheath according to claim 2, characterized in that, Step (1) Add graphene to an ethanol aqueous solution, disperse it by ultrasonication, add 3-aminopropyltriethoxysilane and adjust the pH to 4-5.5, stir and react at 50°C for 30-60 min to obtain a dispersion; the amount of 3-aminopropyltriethoxysilane added is 5%-15% of the mass of graphene.

5. The fluorosilicone rubber fireproof cable sheath according to claim 2, characterized in that, Step (3) Add tridecafluorooctyltriethoxysilane to the ternary hybrid suspension, adjust the pH to 4-5.5, heat to 50-70℃ in a closed environment, stir and react for 1.5-3h to obtain the product; separate the solid and liquid of the product, dry and pulverize it to obtain the graphene-alumina silica-furan black in-situ hybrid intercalation filler.

6. The fluorosilicone rubber fireproof cable sheath according to claim 2, characterized in that, The method for preparing the sheet-like aluminum silicate includes the following steps: Aluminum sulfate or aluminum chloride is dissolved in deionized water to prepare an aluminum salt solution with a concentration of 0.3-0.8 mol / L; sodium silicate is dissolved in deionized water to prepare a silicon source solution with a concentration of 0.5-1.5 mol / L; the silicon source solution and aluminum salt solution are added dropwise simultaneously and in parallel under stirring in a water bath at 60-80℃. After the addition is complete, urea is added, and stirring is continued for 30-60 min. The pH is then adjusted to 8-9.5 to form a silica-alumina composite gel; the silica-alumina composite gel is subjected to a hydrothermal reaction at 180-220℃ for 12-24 h to obtain the product; the product is washed and dried to obtain a dried material; the dried material is heated to 600-750℃ at a rate of 2-5℃ / min, kept at that temperature for 2-4 h, and then naturally cooled to room temperature to obtain the sheet-like aluminum silicate.

7. The fluorosilicone rubber fireproof cable sheath according to claim 6, characterized in that, In the preparation method of the sheet-like aluminum silicate, hexadecyltrimethylammonium bromide is added along with urea.

8. The fluorosilicone rubber fireproof cable sheath according to claim 1, characterized in that, The halogen-free compound flame retardant filler is a mixture of aluminum hydroxide, zinc borate and phosphate glass in a mass ratio of (4-6):(1-3):(2-4), and is modified with tridecafluorooctyltriethoxysilane.

9. A method for preparing a fluorosilicone rubber fire-resistant cable sheath as described in any one of claims 1-8, characterized in that, Includes the following steps: S1. Mix activated magnesium oxide, graphene-aluminum silicate-silica in-situ hybrid intercalation filler and halogen-free composite flame retardant filler at a rotor linear velocity of 20-35 m / s for 10-15 min to obtain composite filler. S2, plasticize the fluorosilicone raw rubber at 60-75℃ for 3-5 minutes, add composite filler and fluorosilicone oil, and continue to mix for 8-12 minutes, controlling the mixing temperature to ≤90℃ during the process, to obtain the rubber compound; S3, after the rubber compound cools down to below 50℃, add the bis(2,5) vulcanizing agent and TAIC crosslinking agent, and mix for 3-4 minutes to obtain the mixture; S4. The mixture is fed into a two-roll open mill for thin passing 5-8 times at a roller temperature of 40-60℃. After pressing, it is allowed to stand at room temperature for 16-24 hours to obtain the film. S5. The film is extruded and wrapped onto the cable core wire. After wrapping, it is first continuously vulcanized at 170-180℃ for 6-12 minutes, and then vulcanized at 185℃ for 4-5 hours. After cooling and winding, the fluorosilicone rubber fireproof cable sheath is obtained.

10. The method for preparing the fluorosilicone rubber fireproof cable sheath according to claim 9, characterized in that, S2, plasticize the fluorosilicone raw rubber at 60-75℃ for 3-5 minutes, add the composite filler in 2-4 batches, and mix for 1-2 minutes after each batch is added; then add fluorosilicone oil and continue mixing, with a total mixing time of 8-12 minutes, during which the temperature of the mixing chamber is controlled to be ≤90℃, to obtain the rubber compound.

Citation Information

Patent Citations

  • Battery-fluid-resistant fluorinated silicone rubber in-vehicle high-voltage cable sheath material

    CN122037583A